Implementation of The Third Sila Value of Pancasila in the Study of Two Kubu Satu Ormas (Case Study in Karangtengah Garut Village, Kadungora Subdistrict) - Yahya, Rachmi Nursifa; Dewi, Dinie Anggraeni (CV. Media Publikasi Profesional, 2021)
This study aims to determine, analyze, and criticize whether or not Pancasila values ​​have been implemented in Karangtengah Garut Village. The things that will be highlighted are the participation of community groups in Karangtengah Garut Village in implementing the values ​​of Pancasila through various village development activities and analyzing the factors causing the inadequate implementation of Pancasila values ​​and solutions in improving them. This research uses qualitative research with data obtained from book studies, journals, and news relevant to the discussion and then analyzed. Based on this research, it can be concluded that in Karangtengah Garut Village, Pancasila values ​​have been implemented. However, they are still not maximized due to inhibiting factors. There are still many social gaps due to economic problems and because of two camps in ustad in one mosque, pengaji, and mass organizations. Based on the above problems, the authors provide solutions to maintain unity and integrity through the role of village youth through various activities so that Karangtengah Village is more active and innovative in strengthening unity and maximizing the implementation of Pancasila as it should.